Transgender, Mental Health, and Older People: An Appreciative Approach Towards Working Together. (1st December 2016) - Page, Sean; Burgess, Jenny; Davies-Abbott, Ian; Roberts, Debbie; Molderson, Jaanika
Abstract : It cannot be assumed by healthcare providers that transgender people routinely receive care and treatment that is of the quality and sensitivity that should be expected. In particular there are concerns from within the transgender community that they experience discrimination and disrespect from both individual practitioners and the healthcare system as a whole. This causes an avoidance of contact that is undesirable for both users and providers of healthcare services. Older transgender people are vulnerable to a range of mental health problems and, like all elderly, increasingly to dementia; failure to access specialist services in a timely manner may result in unnecessary distress and potentially to crisis. This paper reports on the use of an appreciative inquiry approach towards identifying the opportunities for one health board in North Wales to work more closely with older members of the transgender community it serves.